The Effect of FDI on Indonesia’s Jobs, Wages, and Structural Transformation - Steenbergen, Victor; Hebous, Sarah; Wihardja, Maria Monica; Pradana, Abror Tegar (World Bank, Washington, DC, 2021)
Foreign direct investment (FDI) can provide important opportunities for middle-class jobs by stimulating employment growth, paying wage premiums, and helping to shift workers out of less productive sectors. This analysis exploits regional variations in sales to examine the effect that multinational corporations (MNCs) in the manufacturing sector have on employment and wages in Indonesia between 2007 and 2015. Using interaction effects, it explores how these effects differ by workers’ education level, occupation, and employment status. The study finds that manufacturing MNCs raise average wages in their sector. Yet, higher-educated workers benefit more, and white-collar workers see greater benefits than blue-collar workers. Women also appear to benefit more than men, as a result of the type of labor-intensive sectors MNCs engage in. The study finds evidence that manufacturing FDI can help to accelerate structural transformation, as workers move out of lower-productivity sectors (agriculture and low-skilled services) and into higher-productivity manufacturing.